Integrated approach to radiodiagnosis of follicular thyroid neoplasia: a retrospective cohort trial - L. A. Timofeeva; Yu. K. Aleksandrov; M. A. Yusova; T. N. Aleshina (Кубанский научный медицинский вестник, 2021)
Background. An evidence-based diagnostic tactics for follicular thyroid gland neoplasia is lacking to date. First-line priority are radiography diagnostic techniques, which vary in capacities and therefore must be regulated in use.Objectives. An efficacy evaluation of multiparametric ultrasound (US), sonoelastography (SEG) and radionuclide scintigraphy (RS) in diagnosis of follicular thyroid neoplasms (FTN).Methods. Preoperative examination was interpreted in 222 FTN patients (86 with follicular thyroid adenoma, FTA, and 136 with follicular thyroid cancer, FTC) with subsequent surgery. A retrospective statistical data analysis was performed for B-mode US, colour Doppler imaging (CDI), power Doppler imaging (PDI), sonoelastography and Tc-99m pertechnetate scintigraphy.Results. Novel FTN descriptive evidence has been obtained. Particularly, an FTA vs. FTC trait comparison showed no reliable US marker of a node assignment to FTA or FTC. Trials of the national-manufactured TI-RADS system showed its good diagnostic potential: FTN sensitivity 89.55, specificity 77.58 and accuracy 83.52%. A SEG picture of FTN was typically motley-colour and mosaic. Young’s modulus in FTA was 27.5 ± 7.1 kPa, a higher stiffness (62.1 ± 12.1 kPa) in FTC indicated a higher likelihood of malignancy. Scintigraphy exhibited a modest capacity for FTN diagnosis (sensitivity 86.67, specificity 48.08 and accuracy 56.72%). AUC values (0.617) indicate its limited use for differential FTN diagnosis, mainly in hyperfunctioning nodules. Our experience elaborated an original algorithm for radiographic techniques application in FTN diagnosis.Conclusion. Several radiographic methods are warranted in suspected FTN. First-line is multiparametric US B-mode imaging to detect FTN priority markers and US symptom complexes. Sonoelastography is second-line in ambiguous cases to further clarify structure (stiffness) of the thyroid nodule examined. Unlike SEG, scintigraphy assesses the functional traits of thyroid nodule and so has limited indications, an important factor to consider in FTN.